Pengembangan Strategi Interaksi Model Pembelajaran Flipped Classroom pada Sekolah Menengah Pertama - Hesty Yanti Ningwati; Pardimin Pardimin; Zainnur Wijayanto (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to determine the shortcomings and interaction strategies that will be developed so that the Flipped Classroom-based learning tool becomes an effective learning tool. This research is a qualitative descriptive research. Data collection techniques are interviews, questionnaires and documentation. The results showed that in the video, RPP, LKPD and Module there was input so that the follow-up strategy was to fix the video again with a discussion that was not too fast, improve the video display, improve the composition of core competencies, add pictures to the material, fix question words, command words and writing on RPP, LKPD and Modules, improve study instructions, add columns for student notes, improve module covers, reproduce exercises and concrete examples of questions and improve headers and footers.